Evaluating parking characteristics of park-and-ride facility at Gombak LRT terminal station - Abdul Azeez Kadar Hamsa; Nur Aina Syafiqah Akmal; Zurin Hafika Zolkpeli (Penerbit Universiti Kebangsaan Malaysia, 2021)
Malaysia has been experiencing a rapid increase in the number of private vehicles each year. This has increased in the use of private vehicles for various trip purposes especially work trips. Park-and-ride (PnR) is one of the travel demand management measures that would help to reduce traffic congestion and sustain urban mobility. The success of a park-and-ride facility, however, depends on many factors besides parking characteristics at the public transit stations. This paper evaluates the parking characteristics at one of the rail-based PnR stations of an LRT line. The parking characteristics at the selected rail station were evaluated by applying both a parking utilization survey and a pre-designed questionnaire survey. The parking utilization survey was administered by targeting all the parking spaces at each level of the parking building and a questionnaire survey by targeting a pre-determined sample of parking users. A total of 295 questionnaires were proportionately distributed to the parking users at each level of the PnR facility. The analysis reveals maximum utilization of the parking facility especially during morning and late afternoon hours representing a high proportion of work trip commuters. This finding was well supported when compared with the results from the questionnaire data analysis. There were no clear differences in the parking characteristics between the findings of this study and that of other studies. However, the parking behavior and the pattern of the parkers differ conspicuously from that of other studies. A few recommendations were drawn to overcome the unavailability of parking spaces.